AXIOM: A Hardware-Software Platform for Cyber Physical Systems - Mazumdar, Somnath; Ayguade, Eduard; Bettin, Nicola; Bueno, Javier; Ermini, Sara; Filgueras, Antonio; Jimenez-Gonzalez, Daniel; Martinez, Carlos Alvarez; Martorell, Xavier; Montefoschi, Francesco; Oro, David; Pnevmatikatos, Dionisis; et al. (2016 Euromicro Conference on Digital System Design (DSD), 2016)
Cyber-Physical Systems (CPSs) are widely necessary for many applications that require interactions with the humans and the physical environment. A CPS integrates a set of hardware-software components to distribute, execute and manage its operations. The AXIOM project (Agile, eXtensible, fast I/O Module) aims at developing a hardware-software platform for CPS such that i) it can use an easy parallel programming model and ii) it can easily scale-up the performance by adding multiple boards (e.g., 1 to 10 boards can run in parallel). AXIOM supports task-based programming model based on OmpSs and leverage a high-speed, inexpensive communication interface called AXIOM-Link. Another key aspect is that the board provides programmable logic (FPGA) to accelerate portions of an application. We are using smart video surveillance, and smart home living applications to drive our design.